Thyroid stimulating hormone (TSH) ≥2.5 mU/l in early pregnancy: Prevalence and subsequent outcomes. (March 2017) - Carty, David M.; Doogan, Flora; Welsh, Paul; Dominiczak, Anna F.; Delles, Christian
Abstract: Objective: There remains controversy over how women with abnormal thyroid function tests in pregnancy should be classified. In this study we assessed the proportion of women with thyroid stimulating hormone (TSH) ≥ 2.5 mU/l in a large obstetric cohort, and examined how many have gone on to develop thyroid disease in the years since their pregnancy. Study design: 4643 women were recruited and samples taken in early pregnancy between 2007 and 2010. Thyroid function tests were analysed in 2014; in women with raised TSH computerised health records and prescription databases were used to identify thyroid disease detected since pregnancy. Results: 58 women (1.5%) had a TSH over 5 mU/l and 396 women (10.3%) had TSH between 2.5 and 5 mU/l. Women with TSH > 5mU/l delivered infants of lower birthweight than those with TSH < 2.5 mU/l; there were no other differences in obstetric outcomes between the groups. Of those who have had thyroid tests since their pregnancy, 78% of those with TSH > 5 mU/l and 19% of those with TSH between 2.5 and 5 mU/l have gone on to be diagnosed with thyroid disease. Conclusions: Using a TSH cut-off of 2.5 mU/l in keeping with European and US guidelines means that over 12% of women in this cohort would be classified as having subclinical hypothyroidism. Treatment and monitoring of these women would have major implications for planning of obstetric services.